Identification and characterization of microRNAs from in vitro-grown pear shoots infected with Apple stem grooving virus in response to high temperature using small RNA sequencing. (December 2015) - Liu, Juan; Zhang, XueJiao; Zhang, FangPeng; Hong, Ni; Wang, GuoPing; Wang, Aiming; Wang, LiPing
Abstract Background MicroRNAs (miRNAs) have functions in diverse biological processes such as growth, signal transduction, disease resistance, and stress responses in plants. Thermotherapy is an effective approach for elimination of viruses from fruit trees. However, the role of miRNAs in this process remains elusive. Previously, we showed that high temperature treatment reduces the titers ofApple stem grooving virus (ASGV) from the tips of in vitro-grownPyrus pyrifolia plants. In this study, we identified high temperature-altered pear miRNAs using the next generation sequencing technology, and futher molecularly characterized miRNA-mediated regulaton of target gene expression in the meristem tip and base tissues of in vitro-grown, ASGV-infected pear shoots under different temperatures. Results Using in vitro-grownP. pyrifolia shoot meristem tips infected with ASGV, a total of 22, 592, 997 and 20, 411, 254 clean reads were obtained from Illumina high-throughput sequencing of small RNA libraries at 24 °C and 37 °C, respectively. We identified 149 conserved and 141 novel miRNAs. Seven conserved miRNAs and 77 novel miRNAs were differentially expressed at different temperatures. Target genes for differentially expressed known and novel miRNAs were predicted and functionally annotated. Gene Ontology (GO) analysis showed that high-ranking miRNA target genes were involved in metabolic processes, responses to stress, and signaling, indicating that these high temperature-responsive miRNAs have functions in diverse gene regulatory networks. Spatial expression patterns of the miRNAs and their target genes were found to be expressed in shoot tip and base tissues by qRT-PCR. In addition, high temperature reduced viral titers in the shoot meristem tip, while negatively regulated miRNA-mediated target genes related to resistance disease defense and hormone signal transduction pathway were up-regulated in theP. pyrifolia shoot tip in response to high temperature. These results suggested that miRNAs may have important functions in the high temperature-dependent decrease of ASGV titer in in vitro-grown pear shoots. Conclusions This is the first report of miRNAs differentially expressed at 24 °C and 37 °C in the meristem tip of pear shoots infected with ASGV. The results of this study provide valuable information for further exploration of the function of high temperature-altered miRNAs in suppressing viral infections in pear and other fruit trees.